Түүхэн хүн ам зүйн шинжлэх ухаан - Урангуа, Жамсран (Historia Mongolarum, 2008)
Түүхэн хүн ам зүйн ухааны тухай товч ойлголт, түүний хөгжилт. Хүн ам зүйн судалгаа болон түүхэн судалгааны харилцан нөхцөлт. Түүхэн хүн ам зүйн ухааны эх сурвалжууд. Монгол улс дахь хүн ам зүйн судалгааны байдал. In the article, the author introduced a brief history and comprehension of historical demography. The author highlighted relations and connections between demographic and historical researchs and discussed consensus of historical demography. Also brief introduction of Mongolian historcial demography and current development and condition.